Gene expression plasticity evolves in response to colonization of freshwater lakes in threespine stickleback. Issue 13 (19th June 2014) - Morris, Matthew R. J.; Richard, Romain; Leder, Erica H.; Barrett, Rowan D. H.; Aubin‐Horth, Nadia; Rogers, Sean M.
Abstract Phenotypic plasticity is predicted to facilitate individual survival and/or evolve in response to novel environments. Plasticity that facilitates survival should both permit colonization and act as a buffer against further evolution, with contemporary and derived forms predicted to be similarly plastic for a suite of traits. On the other hand, given the importance of plasticity in maintaining internal homeostasis, derived populations that encounter greater environmental heterogeneity should evolve greater plasticity. We tested the evolutionary significance of phenotypic plasticity in coastal British Columbian postglacial populations of threespine stickleback (Gasterosteus aculeatus) that evolved under greater seasonal extremes in temperature after invading freshwater lakes from the sea. Two ancestral (contemporary marine) and two derived (contemporary freshwater) populations of stickleback were raised near their thermal tolerance extremes, 7 and 22 °C. Gene expression plasticity was estimated for more than 14 000 genes. Over five thousand genes were similarly plastic in marine and freshwater stickleback, but freshwater populations exhibited significantly more genes with plastic expression than marine populations. Furthermore, several of the loci shown to exhibit gene expression plasticity have been previously implicated in the adaptive evolution of freshwater populations, including a gene involved in mitochondrial regulation (PPARAa). Collectively, these data provide molecular evidence that highlights the importance of plasticity in colonization and adaptation to new environments.